Electrólisis percutánea intratisular en el tratamiento fisioterapéutico de la tendinitis rotuliana - Christian David, Quiña Manobanda (2021)
ABSTACT Patellar tendonitis, better known as jumper's knee, is the most frequent pathology in athletes and people worldwide. This research aimed to determine the effectiveness of the Percutaneous Electrolysis Intratissue technique by combining some eccentric training and challenging it against traditional treatments. It is mandatory to mention part of the information was obtained by some scientific articles and databases such as Google Scholar, PubMed, Scribd, Research Gate Scielo, Springer Link, and University repository. The whole research was tested with the PEDro Scale to valid only a score of 6 or above and include the positive ones in the presented study. Moreover, two languages, English – Spanish, and only 35 appropriated articles were considered for this work. Consequently, based on the analysis of the scientific articles, it demonstrated that the Percutaneous Electrolysis Intratissue technique combined with eccentric training would become the most effective therapy in treating patellar tendonitis. Keywords: Percutaneous Electrolysis Intratissue, Patellar Tendonitis, Eccentric Training. Reviewed by: Ms.C. Ana Maldonado León ENGLISH PROFESSOR C.I.0601975980